Persepsi Eks-Karyawan Bank Terhadap Praktik Perbankan Syariah - Septriau Putra Abadi; Eja Armas Hardi; Sucipto Sucipto (ITB AAS INDONESIA Surakarta, 2022)
This research aims to discuss banking practices in sharia in terms of actors or ex-employees of sharia banking well as former employees of conventional banking, who have sharia business, to find out whether sharia banking practices have used shariah principles correctly. Retrieval technique the data in this research using qualitative methods with using observation, interview and data analysis technique, namely data collection, data reduction, data presentation, and conclusion drawing. Furthermore, the result of the research is Islamic banking must provide knowledge to employees and the public about Islamic banking rules correctly, Islamic bank product innovation does not only differentiated in terms of language. Recommendation from this research is so that Islamic banks in carrying out their activities banks must apply shariah principles in a 100% kaffah manner, although there are still shortcomings.